An analysis of the Doctrine of Fascism and its contribution to understanding Mussolini's movement - Schargel, Sergio (2023)
Of the many discursive materials created by Mussolini in the Fascist vintenium, few are as rich as the 1932 Doctrine. Published at a time when the regime was seeking to institutionalize and “normalize”, the material is fundamental to the historiography of Fascism for revealing how Mussolini saw his own movement/ideology/regime. This article will offer a content analysis of this material, with the intention of apprehending the main elements that constitute it and their differences or similarities in relation to other moments of Fascism. With the help of Robert Paxton's theory, it will be possible to contribute to the historiography of Fascism, by illuminating the idiosyncrasies of the Doctrine, showing how much the movement/regime has changed over the years ― which makes it difficult to speak in a Fascism with frozen features. In short, to understand what Fascism said about itself, and how much this dialogued with Mussolini’s practice.